Effects of confinement on Espoch marketing students - Pazmiño Garzón, Denise; Delgado Rodríguez, Carlos; Bolaños Logroño, Paulina (mktDESCUBRE; Vol 1 No Especial (2021): Special Edition 4th International Scientific Congress of Administrative and Financial Sciences FADE 2020DO - 10.36779/mktdescubre.v1iEspecial.570, 2021)
The main objective of the present research work was to determine the effects of confinement on students of the Marketing career of the Escuela Superior Politécnica de Chimborazo. The study approach was quali-quantitative, a descriptive, non-experimental and cross-sectional investigation was used, the inductive method was applied; the technique used to collect the information was the online survey shared with the entire student population. The findings reflect that the students miss having contact with nature, there is a lack of concentration, difficulty staying calm, their families face a difficult economic situation, in many cases they have had to face the disease due to the contagion of covid-19, even the loss of family members, events that have caused a high level of concern about the health crisis that is being faced, generating stress, depression and anxiety in most students. In addition to this, there are students who have difficulties accessing virtual classes, they feel overwhelmed by the amount of tasks they have to carry out and they agree that the lack of communication with teachers affects their academic performance; situation that merits the implementation of mitigation plans for the effects of confinement.